Systemic inflammatory response index mediates the association between stroke and hypertension: a cross-sectional study from NHANES 2001 to 2016 - Mingzhu Tang; Fangming Diao; Yaxian Dong; Jianpeng Lin; Tiezhu Wang; Lihua Yang; Xuanming Lai; Xiaolian Chen; Jinxi Zuo; Junyang Xu; Hongting Shi (Frontiers in Neurology)
BackgroundSystemic inflammation plays a vital role in the development of hypertension and stroke. The systemic immune response index (SIRI), calculated from the numbers of neutrophils, monocytes, and lymphocytes, is a promising indicator of immune dysregulation. Yet, its role in mediating the link between hypertension and stroke remains underexplored.MethodsThis study analysed data from 9,699 adults aged ≥20 years from the National Health and Nutrition Examination Survey (NHANES) 2001–2016. We used logistics regression analyses, Receiver Operating Characteristic (ROC) curve analyses, mediation analyses, trend tests, restricted cubic splines (RCS) and stratified by sex, to explore the associations between SIRI, hypertension, and stroke.ResultsSIRI was significantly associated with stroke (adjusted OR = 1.10, 95% CI: 1.00–1.21, p = 0.047). Hypertension was independently linked to both stroke (adjusted OR = 2.06, 95% CI: 1.42–2.99, p < 0.001) and higher SIRI levels (adjusted β = 1.07, 95% CI: 1.03–1.12, p = 0.002). ROC analysis confirmed strong predictive power for hypertension and SIRI in stroke risk assessment. RCS analysis revealed a nonlinear U-shaped relationship between SIRI and stroke in the overall population and males, but a flatter trend in females. SIRI mediated 1.65% of the hypertension-stroke association (p < 2 × 10−16), with a stronger effect in males (3.38%) than females (1.16%).ConclusionHypertension, SIRI, and stroke were closely related, with SIRI partially mediating their association, particularly in males. SIRI might be potential as a biomarker and therapeutic target for stroke prevention in hypertensive individuals.